PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VII SMP NEGERI 5 BUKITTINGGI - Hasanah, Nur; Arief, Ermawati; Noveria, Ena (Universitas Negeri Padang, 2016)
ABSTRACTÂ This research aims to describe the influence model the effect of problem based learning (PBL) the skills of essay writing texposition text class VII SMP Negeri 5 Bukittinggi. The type of this research is quantitative research done using experimental design. The results of this research are three: (1) essay writing skills exposition text before using problem based learning (PBL) model of class VII SMP Negeri 5 Bukittinggi are in qualifying Nearly Enough (HC) with an average value of 54,34, (2) essay writing skills exposition text after using problem based learning (PBL) model of class VII SMP Negeri 5 Bukittinggi are in qualification More than Enough (HC) with an average value of 68,92, and (3) exposition text essay writing skills class VII SMP Negeri 5 Bukittinggi after using the model of problem based learning (PBL) high than before using the model of problem based learning (PBL).Â Kata kunci : pengaruh, model problem based learning (PBL), teks eksposisi